Effect of Nitrogen on Intercropped Radish (Raphanus sativus L.) and Spinach (Spinacia oleracea L.) Productivity under Greenhouse Conditions - Furqoni, Hafith; Mausbach, Jasmine; Fortner, Nathan; Chen, Xinzheng (Chris); Amori, Anthony Akpofure; Rystrom, Zachary (Department of Agronomy and Horticulture, IPB University, 2025)
Due to a rapidly increasing global population and limited arable land, there is a need to increase crop productivity per unit area and optimize resource utilization by plants. One strategy to achieve improved resource utilization is intercropping, whereby two or more crops are grown in mixed or alternating patterns within a block of land. This study aimed to evaluate the effect of nitrogen on radish (Raphanus sativus L.) and spinach (Spinacia oleracea L.) intercropping on crop growth parameters and yield. Intercropped radish and spinach grown in the greenhouse resulted in only one radish-spinach intercrop ratio (50:50) with the same or greater productivity as radish and spinach monocultures, and it did not include an addition of nitrogen. The LER value associated with this treatment was 1.06. However, adding fertilizer resulted in significantly different (P<0.05) leaf numbers, chlorophyll content, and dry biomass of intercropped radish and spinach compared to treatments without fertilizer, except for leaf number in radish. Radish and spinach’s replacement series response curves are concave and convex, respectively, in fertilizer and non-fertilizer treatments. The response curves imply that radish is more aggressive than spinach in intercropping systems. In the only intercrop treatment with an LER>1.0 (50:50 without fertilizer), radish was 2.9 times more competitive than spinach.